Biophysical analysis of facial skin according to skincare practices and gender differences - Nasaruddin, Nur Zalikha; Jamil, Noor Meliza; Mohd Hanif, Nadzira; Zamery, Muhammad Izzuddin (Faculty of Pharmacy, 2025)
There is limited data on the relationship between skincare routines and facial skin biophysical parameters among Malaysians, particularly with respect to gender differences. The objectives of this study are to determine various types of skincare routines among Pharmacy students at UiTM Puncak Alam, to determine the facial skin biophysical profile differences between genders, and to compare the differences in facial skin biophysical properties between three different skincare routines: single, simple, and advance. In this cross-sectional study, 115 pharmacy students at UiTM Puncak Alam underwent biophysical skin measurements including transepidermal water loss (TEWL), skin hydration, elasticity, and melanin content, using an MPA 580 multi-probe adaptor system. The measurements were taken at the submalar region of the left side of the cheek. There is a significant correlation between skincare routine and skin condition. The advance routine group recorded the lowest TEWL (11.66 ± 2.16 g/h/m²) and highest skin hydration (63.59 ± 11.34 AU) and elasticity (0.90 ± 0.03 AU) compared to simple and single routine groups (p < 0.001). No significant differences were observed in melanin content among the routine groups. Gender analysis revealed that males had higher skin hydration and melanin content compared to females (p < 0.05). In conclusion, skincare routine type and gender influence skin biophysical characteristics, emphasizing the importance of tailored skincare practices for maintaining optimal skin health.